Towards tackling the sustainability system implementation challenges - Miekkoniemi, Mikko (2025)
This research delves into the multifaceted challenges of implementing sustainability systems, particularly focusing on Life Cycle Assessment (LCA) and its inherent data management intricacies. The study employs a Design Science Research (DSR) methodology to develop and evaluate a novel solution to ad-dress the identified challenges. The key finding is that data management presents a significant obstacle in the implementation of LCA systems, with traditional IT governance models often failing to address this critical domain adequately. Data quality emerges as a pivotal factor influencing the successful execution of LCA calculations. The research proposes the Aligned Data Governance Framework (ADGF) as a solution to these challenges. The framework encompasses: clearly defined roles and responsibilities for data governance, standardized processes, tools for monitoring and enhancing data quality. Expert interviews corroborate the potential of the ADGF model to mitigate data management challenges. This research contributes to the understanding of data governance in sustainability initiatives and offers practical guidance for organizations implementing LCA systems.